Holding Health Care Accountable: A Solution to Mitigate Medical Malpractice in Pakistan - Dayan, Fazli; Gulaly, -; Muhammad Sheraz, Mian; ul-Haq, Muhammad Zia (International Journal of Human and Health Sciences (IJHHS), 2020)
Medical malpractice negatively affects the health care across the globe, and the case of Pakistan is not a novel. Beyond the human consequences such as injuries, loss of lives, complete or partial impairment of limbs, including the factors of miseryand violence against health care has far reaching, long-term consequences which affecting the patients trust on the health-care servicesthat has negative and catastrophic impacts on the public health. Indeed, malpractice results from breach of duty on the part of medical practitioner that could be negligence attracting penalty in form of damages, or be recklessness, or deliberate misconduct call for imposition of fine, or physical punishment or both, which serve as detriment for health care provider and as a relief for the aggrieved.Assertively, in theabsence of research studies, the present endeavor was to attract the attention of government andlaw makers towards this issue. And thus, for this purpose, the study was conducted in Peshawar district from July 17th, 2019 to October 1st, 2019. Consequently, the finding of this study reflected the magnitude of non-reporting of sentinel events, unawareness among massesoflaws and remedies that could be availed at the times of malpractice complaints, and key gaps in laws, system and policies of health care dealing with malpractice. The study further demonstrates that prevention as well as establishment of fair and unbiased system of accountability is the need of the day. Since, in this way, the policy and law makers will be enabled to bring reforms in health care system in order to mitigate medical malpractice in Pakistan. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 161-173